Processing of emotional information in the human subthalamic nucleus. Issue 12 (25th October 2012) - Buot, Anne; Welter, Marie-Laure; Karachi, Carine; Pochon, Jean-Baptiste; Bardinet, Eric; Yelnik, Jérôme; Mallet, Luc
Abstract : Background: The subthalamic nucleus (STN) is an efficient target for treating patients with Parkinson's disease as well as patients with obsessive–compulsive disorder (OCD) using high frequency stimulation (HFS). In both Parkinson's disease and OCD patients, STN-HFS can trigger abnormal behaviours, such as hypomania and impulsivity. Methods: To investigate if this structure processes emotional information, and whether it depends on motor demands, we recorded subthalamic local field potentials in 16 patients with Parkinson's disease using deep brain stimulation electrodes. Recordings were made with and without dopaminergic treatment while patients performed an emotional categorisation paradigm in which the response varied according to stimulus valence (pleasant, unpleasant and neutral) and to the instruction given (motor, non-motor and passive). Results: Pleasant, unpleasant and neutral stimuli evoked an event related potential (ERP). Without dopamine medication, ERP amplitudes were significantly larger for unpleasant compared with neutral pictures, whatever the response triggered by the stimuli; and the magnitude of this effect was maximal in the ventral part of the STN. No significant difference in ERP amplitude was observed for pleasant pictures. With dopamine medication, ERP amplitudes were significantly increased for pleasant compared with neutral pictures whatever the response triggered by the stimuli, while ERP amplitudes to unpleasant pictures were not modified. Conclusions: These results demonstrate that the ventral part of the STN processes the emotional valence of stimuli independently of the motor context and that dopamine enhances processing of pleasant information. These findings confirm the specific involvement of the STN in emotional processes in human, which may underlie the behavioural changes observed in patients with deep brain stimulation.